Perancangan Aplikasi Mobile E-Voting Dengan Framework Flutter Untuk Pemilihan Ketua BEM Universitas Esa Unggul Kampus Tangerang - Muhamad Magfur; Nizirwan Anwar (Ikatan Ahli Informatika Indonesia, 2023)
In this research, accompanied by rapid technological advancements, the event of selecting the Student Executive Board (BEM) Chairman faces numerous challenges that can hinder its smooth execution. These challenges include manual voting processes, time-consuming vote counting, inadequate audit trails for voting results, and the added complexity of the Covid-19 pandemic, which has made it difficult to find solutions for conducting the elections. The researcher aims to develop a mobile E-voting application to minimize these obstacles and reduce the time and excessive paper expenditure in the execution of the Student Executive Board (BEM) Chairman elections at Esa Unggul Tangerang Campus. The design of this application utilizes the Extreme Programming (XP) methodology and employs the Dart programming language with the Flutter framework. To ensure the smooth operation of the application, a storage medium, commonly referred to as a database, is necessary. The database used in this research is called Firebase, which is a storage service created by Google that simplifies the researcher's task in developing the Mobile E-voting application. This research highlights the importance of using E-voting in elections, with the potential to expedite the process, reduce costs, enhance efficiency, and improve transparency.